Asexual Blood-Stage Malaria Vaccine Candidate PfRipr5: Enhanced Production in Insect Cells - Correia, Ricardo; Fernandes, Bárbara; Castro, Rute; Nagaoka, Hikaru; Takashima, Eizo; Tsuboi, Takafumi; Fukushima, Akihisa; Viebig, Nicola K.; Depraetere, Hilde; Alves, Paula M.; Roldão, António (Frontiers in Bioengineering and Biotechnology, 2022)
The malaria asexual blood-stage antigen PfRipr, as well as its most immunogenic fragment PfRipr5, have recently arisen as promising vaccine candidates against this infectious disease. Continued development of high-yielding, scalable production platforms is essential to advance malaria vaccine research. Insect cells have supplied the production of numerous vaccine antigens in a fast and cost-effective manner; further improving this platform could prove key for its wider use. In this study, insect (Sf9 and High Five) and human (HEK293) cell hosts as well as process optimizing strategies (new baculovirus construct designs and culture temperature shift to hypothermic conditions) were employed to improve the production of the malaria asexual blood-stage vaccine candidate PfRipr5. Protein expression was maximized using High Five cells at CCI of 2 x106 cell/mL and MOI of 0.1 pfu/cell (production yield = 0.49 mg/mL), with high purity PfRipr5 binding to a conformational anti-PfRipr monoclonal antibody known to hold GIA activity and parasite PfRipr staining capacity. Further improvements in PfRipr5 expression were achieved by designing novel expression vector sequences and performing culture temperature shift to hypothermic culture conditions. Addition of one alanine (A) amino acid residue adjacent to the signal peptide cleavage site and a glycine-serine linker (GGSGG) between the PfRipr5 sequence and the purification tag (His6) induced a 2.2-fold increase in the expression of secreted PfRipr5 over using the expression vector with none of these additions. Performing a culture temperature shift from the standard 27 °C to 22 °C at the time of infection improved PfRipr5 expression by up to 1.7-fold. Notably, a synergistic effect was attained when combining both strategies, enabling to increase production yield post-purification by 5.2-fold, with similar protein quality (i.e. purity and binding to anti-PfRipr monoclonal antibody). This work highlights the potential of insect cells to produce the PfRipr5 malaria vaccine candidate and the importance of optimizing the expression vector and culture conditions to boost expression of secreted proteins.